Live and let's live: psychosocial issues in parent-adolescent conflict (2004)
"This study investigated adolescent impulsivity, parenting styles and marital satisfaction as determinants of parent-adolescent conflict in the home. 120 adolescents and 120 parents drawn from Lagos and lbadan were used in the study. 5 scales were used in data collection: Onuoha (2001) authoritative/authoritarian parenting styles scale, Emelogu (2002) parent-adolescent conflict scale (adolescent version), Olapegbo-Emelogu (2002) adolescent impulsivity scale, Mehrbian (1998) marital satisfaction scale and parent version of the parent-adolescent conflict scale by Emelogu (2002). 2-way ANOVA and Pearson r were used in analyzing the data. There was significant interaction of adolescent impulsivity, authoritative parenting and marital satisfaction on parent-adolescent conflict. The results as well revealed that authoritarian parenting is significantly related to parent-adolescent conflict. It is therefore suggested that a good conflict management mechanism be put in place to reduce conflict to a manageable level. "